Un panorama sullo stato laico e sulle sue implicazioni nel modello brasiliano (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. La religione e la vita nella società - 3. Quello che il principio di laicità non è - 4. Lo Stato laico brasiliano - 5. Considerazioni finali.The secular State and its implications on the brazilian modelABSTRACT: For many years Law and Religion were subjects considered unnecessary by some, and, by others, analyzed with reservations and featured as a not legal topic. However, both of the matters has become important issues in the political, legal and social discussions, especially during political campaign, when moral, ethical and religious issues are brought to debate. Although many countries, as Brasil - for example, have been disussing the subject, the numerous and different interfaces between them, most of the time do not take into consideration the constitutional foundations, axiological and cultural values, and pasrticularly the spiritual aspect of the human being as the structuring of human life. Therefore, the purpose of this article is to clarify the conceptual unfolding of the Principle of Secularity and the characterization of the Secular State in Brazil, with the aim of demonstrating that the Brazilian model of Secularity does not mean the absence of religiosity in the public sphere, but the guarantee and safeguard all your expressions.